Monitoring the Variability of the Pollutant Level in Urban Water Front during Dry and Wet Seasons - Tegu, Tuebi Benson; Ekemube, Raymond Alex; Ebenezer, Sure Olusegun; Atta, Adekunle Temidayo (European Journal of Applied Sciences, 2023)
The variability of the physicochemical properties of River water during the dry season (DS) and rainy season (RS) were carried out using Bonny Water Front Creek (BWFC) as case study. The levels of physicochemical properties including: pH, temperature (T), electrical conductivity (EC), turbidity, salinity, biochemical oxygen demand (BOD), chemical oxygen demand (COD), dissolved oxygen (DO), total dissolved solids (TDS), salinity, polycyclic aromatic hydrocarbon (PAH), iron (Fe), lead (Pb), chromium (Cr) and mercury (Hg), vanadium (V), magnesium (Mg), cadmium (Cd), and nickel (Ni) were analyzed. Water samples were collected along the coastal line in the direction of flow of the water at intervals of 10m from the pollution source up to 100 meters on the water surface with the aid of boat moving from the upstream to downstream in the direction of water flow. The experimental results showed the average concentration of pH (7.52), EC (22355.00µs/cm), T(30.14OC), turbidity (11.64NTU), Salinity (18.91mg/l), B0D(18.07mg/l), COD (55.10mg/l), DO (4.29mg/l), TDS (16.26mg/l), The pH values were within acceptable range, EC, turbidity, TDS, and salinity were above WHO acceptable limit of 1000s/cm, 5NTU, 24-28, N/S, respectively. Also, BOD and COD concentration equally indicated that the Creeks were polluted. Similarly, the concentrations of some heavy metals in the creeks during both seasons were higher than limits given by World Health Organization for river water. Therefore, suggesting for continuous assessment and remedial techniques or treatment process must be applied to ascertain pollutant levels in the creeks to inhabit aquatic life.